The efficacy and safety of sacubitril/valsartan compared with ACEI/ARB in the treatment of heart failure following acute myocardial infarction: a systematic review and meta-analysis of randomized controlled trials - Gao, Jinquan; Zhang, Xin; Xu, Mengzhuo; Deng, Shisu; Chen, Xiaoping (Frontiers in Pharmacology, 2023)
Purpose To systematically assess the efficacy and safety of sacubitril/valsartan (SV) by comparison with angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) for the treatment of heart failure caused by acute myocardial infarction (HF-AMI) based on current randomized controlled trials (RCTs). Methods Several electronic databases were searched up to May 27, 2023. Primary endpoints were the efficacy including the left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDD), N-terminal pro-B type natriuretic peptide (NT-proBNP) and 6-minute walk test (6MWT) and secondary endpoints were the safety including the major adverse cardiovascular event (MACE) and adverse reaction (AE). Results A total of 14 RCTs were included and all patients were from China. Among included 1,991 patients, 997 patients received SVs and 994 patients received ACEIs/ARBs. The pooled results demonstrated that patients in the SV group showed significantly better efficacy representing as increased LVEF [weighted mean difference (WMD): 4.43%, 95% confidence interval (CI): 2.84%~6.02%, P＜0.001] and 6MWT (WMD: 30.84m, 95% CI: 25.65m~36.03m, P＜0.001) and decreased LVEDD (WMD: -3.24mm, 95% CI: -4.96mm~-1.52mm, P＜0.001) and NT-proBNP (WMD: -188.12pg/ml, 95% CI: -246.75pg/ml~-129.49pg/ml, P＜0.001), which was also verified by subgroup analysis based on the history of percutaneous coronary intervention (PCI). Besides, the SV group showed significantly lower incidence rate of MACE [relative risk (RR): 0.60, 95% CI: 0.47~0.75, P＜0.001] and patients receiving SVs in the non-PCI group also showed lower incidence of AE (RR: 0.38, 95% CI: 0.20~0.71, P=0.002). Conclusion For the treatment of HF-AMI, SV is more effective and safer than ACEI/ARB based on current evidence, but more high-quality RCTs are still needed to verify above findings.